2004
DOI: 10.1155/2004/216243
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Electrocautery and Argon Plasma Coagulation: A Practical Approach

Abstract: The present review covers the technical and practical aspects of endobronchial electrocautery, including argon plasma coagulation, which have great potential for widespread use by pulmonologists around the world. The various electrocautery modes, power settings and electrode probes are described in detail, and the authors' clinical and technical approach is demonstrated with a narrative description and brief case presentations. Malignant airway obstruction, hemoptysis, web-like stenosis, stent related granulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 21 publications
0
47
0
2
Order By: Relevance
“…If used in the treatment of post-intubation tracheal stenosis EC and APC can be fibro-genetic and Cryo is ineffective because of the lack of blood vessels; moreover it can be dangerous for the possible persistence of iced tissue in the airways. These methods, especially APC, may only be used in granulomas [17][18][19] (Level of evidence: III).…”
Section: Electrocauterication (Ec) Argon-plasmamentioning
confidence: 99%
“…If used in the treatment of post-intubation tracheal stenosis EC and APC can be fibro-genetic and Cryo is ineffective because of the lack of blood vessels; moreover it can be dangerous for the possible persistence of iced tissue in the airways. These methods, especially APC, may only be used in granulomas [17][18][19] (Level of evidence: III).…”
Section: Electrocauterication (Ec) Argon-plasmamentioning
confidence: 99%
“…Recently, APC has been used in the treatment of benign or malignant lesions in the airway [5][6][7]. It has an excellent safety profile, is convenient and simple to use, and is relatively inexpensive.…”
Section: Discussionmentioning
confidence: 99%
“…Argon plasma coagulation (APC) has recently been widely used in tracheobronchial disease [5,6] because it allows a rapid coagulation with minimal manipulation and mechanical trauma to the target tissue [6]. A previous study reported the safety efficacy of APC for the management of airway stenosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…High-frequency electric current is delivered to the malignant stenosis, using a monopolar mode, by means of a flexible or rigid probe of varying diameter and form, such as a coagulation electrode, loop [12,21] or hot biopsy forceps. New-generation generators can be set to different modes [22]. In the "soft coagulation" mode, the heat produced does not exceed 200°C and no electric arc is generated, thus preventing tissue from carbonisation and ignition or airway fire, unlike the "forced coagulation" mode.…”
Section: Lasermentioning
confidence: 99%
“…In the "soft coagulation" mode, the heat produced does not exceed 200°C and no electric arc is generated, thus preventing tissue from carbonisation and ignition or airway fire, unlike the "forced coagulation" mode. Electrocautery equipment (generator and probes) is far less expensive than laser [22][23][24]. The symptom improvement observed is constant (96%) and results in a gain of 53% in FEV1 [25], equivalent to that obtained with [22,25].…”
Section: Lasermentioning
confidence: 99%